The Role of Participatory Leadership in Developing Creativity and Increasing Teachers' Motivation toward Teaching in Saudi Schools - Tahani Moussa Al- Fayez (Taez University, 2024)
This study examines the relationship between participatory leadership, creativity development, and teacher motivation in Saudi schools, addressing a gap in the theoretical literature. The aim of this study is to understand how leadership styles impact educational outcomes. A descriptive quantitative research design was utilized, involving a thorough review of relevant literature and the administration of a closed-ended questionnaire to a sample of 100 teachers. The questionnaire was designed based on previous studies and validated through a pilot study, achieving a Cronbach's alpha of 0.897 for overall reliability. The results indicate a strong positive relationship between participatory leadership and both creativity development and teacher motivation, with a correlation coefficient of 0.974 (p = 0.000). This finding is consistent with existing literature that emphasizes the benefits of collaborative decision-making and professional development in enhancing job satisfaction and organizational success. The high level of agreement among teachers (mean = 4.09) underscores the significance of participatory leadership in fostering a supportive and innovative educational environment. In conclusion, the study highlights the pivotal role of participatory leadership in enhancing teacher motivation and creativity, which are essential for improving educational outcomes in Saudi schools. The study recommends that school principals adopt participatory practices, involve teachers in decision- making, and offer professional growth opportunities. Training programs on participatory leadership should be implemented, and further research should examine the long- term impacts on student performance and overall school effectiveness.